Aspergillus empyema in a patient with hydropneumothorax: Unveiling the exceptional - Jangla, Sunayana Mukesh; Cherian, Susan (Indian Journal of Case Reports, 2025)
Pleural aspergillosis is an unusual form of invasive aspergillosis. A 67-year-old female presented with breathlessness, and a catheter inserted on the left side of the chest for draining pleural fluid. The drained pleural fluid was indicative of empyema and showed growth of Aspergillus flavus. Treatment with isavuconazole improved her condition. She had history of pleural tuberculosis and developing hydro-pneumothorax in recent past.She was on immunosuppresant for autoimmune disorder. This case highlights risk factors associated with invasive aspergillosis and emphasizes that such an exceptional condition should be considered a differential diagnosis, especially amidst the above medical background. Equally important is to note that newer and better drugs pave the way for efficient patient management.